Anti-rust layer, manufacturing method thereof and cooker
By applying a multi-layer sub-layer anti-rust layer on the iron pot, the gap structure of micro- and nano-scale gaps is used to solve the problem of rust easily, and better corrosion resistance and non-stick properties are achieved.
Patent Information
- Application Number
- CN202411668449.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-03-11
AI Technical Summary
Iron pots are prone to rust, which affects the user experience, and the existing anti-rust layer has insufficient anti-rust performance.
The anti-rust layer of a plurality of sub-layers arranged laminated, each sub-layer has a gap structure, formed by stacking a plurality of microscale materials, the microscale materials are formed by stacking a plurality of nanoscale scales, the gap structure has a plurality of microscale gaps and nanoscale gaps, and the sub-layers are arranged interlaced in the thickness direction.
Effectively block corrosive media such as water vapor, acid, and salt, improve the corrosion resistance of cookware, and enhance non-stick properties.
Smart Images

Figure CN119592948A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of non-stick cookware, and more specifically, to an anti-rust layer for cookware and a manufacturing method thereof, and the cookware. Background Art
[0002] Iron pans are popular among consumers due to their many advantages, especially in Chinese cooking, where the heat conductivity and wear resistance of iron pans make them an ideal choice for cooking methods such as stir-frying. However, the problem of iron pans being prone to rust also brings inconvenience to consumers and affects their user experience.
[0003] Therefore, developing an anti-rust layer with better anti-rust performance is still a problem that needs to be solved. Summary of the invention
[0004] Therefore, the purpose of the present application is to provide an anti-rust layer for cookware and a manufacturing method thereof, and cookware, so as to solve the problem that the existing iron pan is prone to rust.
[0005] According to a first aspect of the present application, there is provided an anti-rust layer for use in cooking utensils, wherein the anti-rust layer comprises a plurality of stacked sub-layers, the sub-layers having a layer gap structure, the layer gap structure being formed by stacking a plurality of micro-scale flaky materials, the micro-scale flaky materials being formed by stacking a plurality of nano-scale flakes, the layer gap structure having a plurality of micron-scale gaps, and a plurality of nano-scale gaps between adjacent micron-scale gaps, wherein the layer gap structures of the respective sub-layers are arranged alternately in a thickness direction of the anti-rust layer.
[0006] According to the anti-rust layer provided by the embodiment of the present application, multiple micro-scale flaky materials can form a criss-cross interlayer structure (similar to the stack formed by the arrangement of fish scales) by stacking, and the formed multi-layer interlayer structure is staggered in the thickness direction, so that the anti-rust layer as a whole forms a physical barrier layer, which can effectively prevent water vapor, acid, salt and other corrosive media from penetrating toward the base material of the cookware, thereby avoiding affecting the base material of the cookware. At the same time, the anti-rust layer itself has good corrosion resistance, and even if water vapor, acid, salt and other corrosive media exist on the surface of the anti-rust layer, the cookware will not be corroded, so that the corrosion resistance of the cookware can be guaranteed.
[0007] In some embodiments, the size of the micron-scale gap is 1 micron-10 microns, the size of the nano-scale gap is 50 nanometers-200 nanometers, and the anti-rust layer having a layer structure of micron-scale gaps and nano-scale gaps of the above sizes has a higher uniformity of the layer structure and can have relatively excellent corrosion resistance. And / or the nano-scale gaps and the micron-scale gaps are irregular shapes. Compared with regular gap structures, irregular shapes can provide more surface changes and spatial distributions. On the one hand, it helps the staggered arrangement of the layer structure in the thickness direction to further enhance the anti-rust ability. On the other hand, it helps the gas (such as air and water vapor) to be more evenly distributed and expanded in the gap, thereby forming a uniform and stable air flotation effect, so that the anti-rust layer also has good non-stick properties.
[0008] In some embodiments, the micro-scale flake material is a micron-scale flake, and the surface area of the micron-scale flake is 50 square microns-3600 square microns, and the thickness is 1 micron to 5 microns.
[0009] In these embodiments, micron-sized flakes with a specific surface area and thickness can effectively micro-melt and accumulate to form an anti-rust layer under the action of a subsequent energy source, matching the subsequent energy source, thereby facilitating the optimal performance of the anti-rust layer.
[0010] In some embodiments, the surface area of the nanoscale flakes is 4900 square nanometers to 360000 square nanometers, and the thickness is 10 nanometers to 50 nanometers. In this way, a micron-scale flake with a predetermined gap can be constructed, so that the anti-rust layer formed by the micron-scale flakes has a desired interlaminar structure, thereby achieving the purpose of improving the anti-rust ability of the anti-rust layer. And / or in the micro-scale flaky material, the gap between adjacent nanoscale flakes is in the range of 50 nanometers to 200 nanometers. By selecting a micro-scale flaky material with a suitable nanoscale flake gap, the desired interlaminar structure can be easily obtained. In the process of forming the anti-rust layer, the micro-scale flaky material has a relatively stable structure and is not prone to large deformation or reorganization, so that the original gap characteristics can be maintained. Since the nanoscale gaps in the micro-scale flaky material are retained, the nanoscale gaps in the interlaminar structure of the anti-rust layer formed can also be guaranteed. This optimized interlaminar structure helps to reduce the immersion path of the corrosive medium and improve the anti-rust performance of the anti-rust layer. In addition, the presence of nanoscale gaps can also improve the durability of the anti-rust layer. Since the size of the gaps in the anti-rust layer of the present application is very small, the corrosive medium will encounter great resistance when passing through, making it difficult for the corrosive medium to penetrate. In addition, the nanoscale gaps between the micro-scale flaky materials can also increase the adhesion between the anti-rust layer and the substrate. When the anti-rust layer is formed, these gaps can be embedded in the substrate surface like "anchor points", thereby improving the overall bonding strength of the anti-rust layer.
[0011] In some embodiments, the micro-scale flaky material is an inorganic non-metallic material having a certain hardness and high temperature resistance, so that the formed anti-rust layer can remain stable under high temperature and wear environment.
[0012] In some embodiments, the inorganic non-metallic material includes micaceous iron oxide or a modified product of micaceous iron oxide. The above materials have low surface energy and high wear resistance, which can ensure that the anti-rust layer formed by them has a certain non-stick durability. In a preferred embodiment, the micaceous iron oxide is gray micaceous iron oxide, which can ensure that the formed anti-rust layer has a relatively dark color, thereby enhancing the dirt resistance and user experience of the cookware.
[0013] In some embodiments, the thickness of the anti-rust layer is 10 microns to 150 microns, so that the properties of the cookware in terms of weight, non-stickiness, thermal conductivity, etc. can be balanced, so that the overall performance of the cookware is better.
[0014] In some embodiments, the hardness of the anti-rust layer is 600HV to 1100HV. The anti-rust layer of such hardness can balance wear resistance and flexibility, having sufficient wear resistance to resist scratches and abrasion, and maintaining good flexibility to avoid cracking or peeling under temperature changes or mechanical stress. And / or, the anti-rust layer has a temperature tolerance of 800℃-1200℃, so that the cookware with the anti-rust layer can withstand high temperatures and has longer durability.
[0015] In some embodiments, a fatty acid salt modified layer is connected to the surface of the anti-rust layer, and the fatty acid salt modified layer includes fatty acid salts formed by chemical bonding of oil and fat with metal elements contained in the surface of the anti-rust layer.
[0016] In these embodiments, a fatty acid salt modified layer is further connected to the surface of the anti-rust layer. The fatty acid salt modified layer is compatible with oils and fats, so by utilizing the oil film non-stick principle, the initial non-stick property and the lasting non-stick performance of the cookware are improved to a certain extent.
[0017] In some embodiments, the oil comprises at least one of glyceryl stearate, glyceryl palmitate and glyceryl oleate.
[0018] In these embodiments, the grease can be connected to the surface of the anti-rust layer and can have a low surface energy after forming corresponding salts, thereby further improving the initial non-stick property and the long-lasting non-stick performance of the cookware.
[0019] According to a second aspect of the present application, a method for manufacturing an anti-rust layer is provided, wherein the method comprises the following steps:
[0020] Providing a micro-scale material, wherein the micro-scale material is formed by stacking a plurality of nano-scale flakes;
[0021] Micro-melting the surface of the micro-scale material to form a rust-proof layer having a plurality of sub-layers stacked in a thickness direction by stacking the micro-scale material, and making the interlayer structures of the sub-layers arranged in a staggered manner in the thickness direction of the rust-proof layer;
[0022] The sublayer has a layer gap structure, the layer gap structure has a plurality of micrometer-level gaps, and a plurality of nanometer-level gaps are provided between adjacent micrometer-level gaps.
[0023] According to the method for manufacturing the anti-rust layer provided in the embodiment of the present application, by using a specific micro-scale flaky material for micro-melting treatment, the micro-scale flaky material is stacked in layers to form an anti-rust layer having the above-mentioned specific interlayer structure and interlayer distribution, and the formed multi-layer interlayer structure is staggered in the thickness direction, so that the anti-rust layer as a whole is formed into a physical barrier layer, which can effectively prevent water vapor, acid, salt and other corrosive media from penetrating toward the base material of the cooker, thereby avoiding affecting the base material of the cooker. At the same time, the anti-rust layer itself has good corrosion resistance, and even if water vapor, acid, salt and other corrosive media exist on the surface of the anti-rust layer, the cooker will not be corroded, so that the corrosion resistance of the cooker can be guaranteed.
[0024] In some embodiments, the step of slightly melting the surface of the micro-flaky material includes: heating the micro-flaky material with plasma, supersonic flame, electric arc or laser as an energy source to slightly melt the surface of the micro-flaky material.
[0025] In these embodiments, the anti-rust layer can be adapted to be formed by various types of heat sources, thereby being able to broaden the methods of manufacturing the anti-rust layer.
[0026] In some embodiments, the plurality of sub-layers are respectively formed of micro-scale materials of different sizes, so that the interlayer structures of the sub-layers are arranged alternately in the thickness direction of the anti-rust layer.
[0027] In these embodiments, micro-flake materials of different sizes can be used to form sub-layers with different layer gap structures, so that the layer gap structures of each sub-layer are arranged alternately in the thickness direction of the anti-rust layer, and the anti-rust layer can be obtained as a barrier layer, and this method is easy to control.
[0028] Specifically, the micro-flaky materials of different sizes include a plurality of first micron-sized flakes and a plurality of second micron-sized flakes, wherein the surface area of the first micron-sized flakes is greater than the surface area of the second micron-sized flakes, and the thickness of the first micron-sized flakes is greater than the thickness of the second micron-sized flakes; wherein a first sublayer is formed on a substrate by the first micron-sized flakes, and then a second sublayer is formed on the first sublayer by the second micron-sized flakes, so that the interlayer structures of the sublayers of the anti-rust layer are arranged alternately in the thickness direction of the anti-rust layer; or, a first sublayer is formed on a substrate by the second micron-sized flakes, and then a second sublayer is formed on the first sublayer by the first micron-sized flakes, so that the interlayer structures of the sublayers of the anti-rust layer are arranged alternately in the thickness direction of the anti-rust layer.
[0029] In these embodiments, the size of the micro-flaky material forming the relatively inner layer is relatively larger, and the size of the micro-flaky material forming the relatively outer layer is relatively smaller, or the size of the micro-flaky material forming the relatively inner layer is relatively smaller, and the size of the micro-flaky material forming the relatively outer layer is relatively larger. In this way, the gaps between the sub-layers of the formed anti-rust layer can be staggered in the thickness direction. In this way, the gaps between the sub-layers of the anti-rust layer in the thickness direction can not communicate with each other, so that it can act as a barrier layer to prevent the entry of corrosive media, avoid corrosion of the junction between the substrate and the anti-rust layer, and ensure the anti-rust ability of the product with the anti-rust layer.
[0030] In some embodiments, the surface area of the first micron-scale flakes is 50 square microns to 1000 square microns, and the thickness is 1 micron to 3 microns; and / or, the surface area of the second micron-scale flakes is 1000 square microns to 3600 square microns, and the thickness is 3 microns to 5 microns; and / or, the first micron-scale flakes are composed of a plurality of first nanoscale flakes stacked together, the surface area of the first nanoscale flakes is 4900 square nanometers to 90,000 square nanometers, and the thickness is 10 nanometers to 30 nanometers; and / or, the second micron-scale flakes are composed of a plurality of second nanoscale flakes stacked together, the surface area of the second nanoscale flakes is 90,000 square nanometers to 360,000 square nanometers, and the thickness is 30 nanometers to 50 nanometers.
[0031] In these embodiments, the arrangement of the interlayer structure can be further optimized through micro-flake materials with specific parameters to ensure better anti-rust performance.
[0032] According to a third aspect of the present application, a cooker is provided, wherein the cooker comprises a substrate and an anti-rust layer formed on the substrate, and the anti-rust layer comprises the anti-rust layer described above or comprises an anti-rust layer manufactured by the method for manufacturing an anti-rust layer described above.
[0033] In some embodiments, the cookware further includes a transition layer, which is formed of a metal material and is formed between the base and the anti-rust layer.
[0034] In these embodiments, by providing a transition layer, the bonding strength between the anti-rust layer and the substrate can be further improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] The above and / or other features and aspects of the inventive concept will become clear and easily understood through the description of the embodiments in conjunction with the accompanying drawings.
[0036] Figure 1 is a schematic diagram of a cross-sectional structure of a cooker provided in an embodiment of the present application after being cut along the thickness direction;
[0037] Figure 2 yes Figure 1 A schematic diagram of the enlarged structure at position I in the middle;
[0038] Figure 3 is a scanning electron microscope image of the anti-rust layer provided according to an embodiment of the present application;
[0039] Figure 4 is a schematic diagram of the structure of the anti-rust layer provided according to an embodiment of the present application;
[0040] Figure 5 is a schematic diagram of a top view of a micron-scale scale provided according to an embodiment of the present application;
[0041] Figure 6 It is a schematic diagram of the side view structure of the micron-scale flakes provided according to an embodiment of the present application.
[0042] Explanation of symbols:
[0043] 100. Cookware; 110. Base; 120. Anti-rust layer; 130. Transition layer; 10. Micron-scale flakes; 11. Nano-scale flakes. DETAILED DESCRIPTION
[0044] The exemplary embodiments of the inventive concept will be described in more detail below. Although the exemplary embodiments of the inventive concept are described below, it should be understood that the inventive concept can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided only to enable a more thorough understanding of the present invention and to enable the scope of the inventive concept to be fully communicated to those skilled in the art.
[0045] The inventors have discovered that the gap structure of the anti-rust layer can affect the anti-rust performance of the cookware to a certain extent. Therefore, the present application explores the gap structure of the anti-rust layer.
[0046] According to the inventive concept of the present application, a rust-proof layer for cookware is provided, wherein at least the surface layer of the rust-proof layer has a plurality of micro-scale flake materials (flakes) stacked one on another to form a unique interlayer structure. Here, the interlayer structure is similar to a stack of fish scale flakes, the micro-scale flake material is a plurality of micron-scale flakes, and the interior of each micron-scale flake is further composed of a plurality of nano-scale flakes, such micro-scale flake materials have a large surface area and a number of interfaces, which can be conducive to forming a rust-proof layer of the desired interlayer structure. Since the surface layer of the interlayer structure has a plurality of micron-scale gaps, and there are a plurality of nano-scale gaps between adjacent micron-scale gaps, the micron-scale gaps of the interlayer structure are further refined by the nano-scale gaps, so that the entire interlayer structure has a suitable gap size and a uniform gap distribution, and the interlayer structure of the plurality of sub-layers is staggered in the thickness direction, and the whole is formed into a physical barrier layer, which effectively blocks the penetration of corrosive media such as water vapor, acid, and salt in the direction of the base material of the cookware, thereby avoiding affecting the base material of the cookware. At the same time, the anti-rust layer itself has good corrosion resistance. Even if corrosive media such as water vapor, acid, and salt exist on the surface of the anti-rust layer, the cookware will not rust. In this way, the corrosion resistance of the cookware can be guaranteed.
[0047] According to a first aspect of the present application, there is provided an anti-rust layer for use in cookware, formed on a substrate of the cookware, wherein the anti-rust layer comprises a plurality of sub-layers stacked in a thickness direction, the sub-layers having a layer gap structure, the layer gap structure being formed by stacking a plurality of micro-flaky materials, the micro-flaky materials being formed by stacking a plurality of nano-scale flakes, the layer gap structure having a plurality of nano-scale gaps, and a plurality of micro-scale gaps between adjacent nano-scale gaps, wherein the layer gap structures of the respective sub-layers are arranged alternately in a thickness direction of the anti-rust layer.
[0048] In the embodiment of the present application, the micro-scale flaky material refers to a material having a similar scale shape and being micron-sized as a whole. As an example, the micro-scale flaky material is a micron-sized scale, wherein each micron-sized scale includes at least one layer, and each layer is composed of a plurality of nano-sized scales stacked. It can be understood that each micron-sized scale is a primary structure, which also includes a secondary structure (multiple nano-sized scales) that is finer than the primary structure. Here, the primary structure can be regarded as the structure of a single scale macroscopically, and the secondary structure can be regarded as a component constituting the primary structure.
[0049] In some embodiments, the surface area of the micron-scale scale is 50 square microns-3600 square microns (the surface size of the scale is in the range of 7 microns-60 microns), and the thickness is 1 micron to 5 microns. In the micron-scale scale, the surface area of the nanoscale scale is about 1 / 9500-1 / 11000 of the surface area of the micron-scale scale, and the thickness of the nanoscale scale is about 1 / 90-1 / 110 of the thickness of the micron-scale scale. Here, it should be noted that the surface area of the micron-scale scale is the area of the entire outer surface of the micron-scale scale, that is, the sum of the areas of all external surfaces.
[0050] As an example, the surface area of the nanoscale flakes is 4900 square nanometers to 360,000 square nanometers (the size of the nanoscale flakes is 70 nanometers to 600 nanometers), and the thickness is 10 nanometers to 50 nanometers. Here, it should be noted that the surface area of the nanoscale flakes is the area of the entire outer surface of the nanoscale flakes, that is, the sum of the areas of all external surfaces.
[0051] As some examples, the micro-scale material is a single layer of micron-scale scales, and each micron-scale scale is composed of a plurality of scales of smaller sizes. Specifically, each micron-scale scale is composed of a plurality of stacked nanoscale scales.
[0052] As other examples, the micro-scale material is a multi-layer micron-scale flake, each layer of which in the thickness direction is composed of a plurality of scales of smaller sizes. Specifically, each layer of the multi-layer micron-scale flake is composed of a plurality of stacked nanoscale flakes.
[0053] In these embodiments, the preparation method of the single-layer micro-flaky material is simple, and the multi-layer micro-flaky material can have relatively better properties, such as strength, toughness or corrosion resistance.
[0054] In summary, according to the present application, the micro-scale flaky material can have a suitable surface area and number of interfaces, so that a desired anti-rust layer with a layer gap structure can be formed by stacking it in layers.
[0055] According to the rust-proof layer provided by the embodiment of the present application, first, the rust-proof layer is composed of a plurality of sub-layers stacked in the thickness direction, and the micro-scale-like materials inside each sub-layer are arranged in a staggered manner to form a criss-cross interlayer structure. This arrangement can greatly reduce the possibility of forming through holes in the thickness direction of the rust-proof layer, thereby enhancing the corrosion resistance of the rust-proof layer. This is because, even if there are tiny gaps between some micro-scales, since these gaps are staggered between multiple sub-layers, it is difficult for the corrosive medium to continuously penetrate the entire rust-proof layer through these gaps. Secondly, the surface gaps of the rust-proof layer are designed to allow water molecules and / or air to pass through, and can effectively prevent oil molecules from passing through. This design is similar to the natural stacking method of fish scales, and its gap size and distribution can form an air flotation effect. This effect not only helps to keep the rust-proof layer clean and prevent sticky substances such as oil stains from adhering, but also reduces the direct contact between the corrosive medium and the surface of the rust-proof layer to a certain extent, further improving the rust-proof performance. In this way, the interlaced arrangement of the interlayer structure of the multi-layer anti-rust layer in the thickness direction makes the anti-rust layer as a whole form a physical barrier layer, which can effectively prevent water vapor, acid, salt and other corrosive media from penetrating toward the base material of the cookware, thereby avoiding affecting the base material of the cookware. At the same time, the anti-rust layer itself has good corrosion resistance, and even if water vapor, acid, salt and other corrosive media exist on the surface of the anti-rust layer, the cookware will not be corroded, thus ensuring the corrosion resistance of the cookware.
[0056] According to the present application, the gaps of the interlayer structure in the multiple sublayers stacked can be arranged regularly, specifically, they can be arranged from large to small along the thickness direction of the anti-rust layer. When the gaps of the interlayer structure are arranged from large to small along the thickness direction, it means that the sublayer close to the substrate has a larger interlayer gap, while the sublayer close to the surface of the cookware has a smaller interlayer gap. This arrangement helps to form a barrier that gradually becomes denser from the inside to the inside inside the anti-rust layer, thereby more effectively blocking the infiltration of corrosive media. At the same time, since the vicinity of the substrate may be more susceptible to stress and corrosion, a larger interlayer gap can provide additional buffering and adaptability. Of course, the anti-rust layer can also be arranged from small to large along the thickness direction. When the interlayer structure is arranged from small to large along the thickness direction, it means that the sublayer close to the surface of the cookware has a larger interlayer gap, while the sublayer close to the substrate has a smaller interlayer gap. This arrangement may focus more on the infiltration of corrosive media, while allowing the interlayer gap near the substrate to provide certain deformation and adaptability when subjected to stress.
[0057] Both of the above methods can make the anti-rust layer as a whole have fewer through gaps in the thickness direction. Here, through gap refers to the gap connecting the substrate and the outside world. The through gap is the main channel for the corrosive medium to immerse. By reducing the number of through gaps, the anti-corrosion performance of the anti-rust layer can be improved. In addition, it should be emphasized that in the embodiments of the present application, it is not required that all sub-layers have interlayer structures and interlayer distributions of each layer. In fact, according to specific application requirements and material properties, only some sub-layers of the surface layer can be selected for the design of the interlayer structure, and this setting is not limited to the overall structure of the anti-rust layer. Under the guidance of the present application, those skilled in the art can make certain deformations and adjustments to the anti-rust layer structure of the present application to achieve the best anti-corrosion effect.
[0058] According to the present application, the micro-scale flake material is a micron-scale flake, which is itself formed by stacking a plurality of nano-scale flakes, and adjacent nano-scale flakes are stacked in an alternating manner to form a micron-scale flake.
[0059] Figure 5 It is a schematic diagram of the top view structure of the micron-scale flakes provided according to the embodiment of the present application. Figure 6 is a schematic diagram of the side view structure of the micron-scale flakes provided in the embodiment of the present application. Figure 5 As shown, a micron-scale scale 10 is composed of a plurality of nano-scale scales 11 at the nanometer level. Specifically, adjacent nano-scale scales 11 are stacked in layers to form a micron-scale scale 10. Figure 6 As shown, it can be seen that the micron-sized scales 10 having a multi-layer structure are arranged in layers in the thickness direction thereof.
[0060] In some embodiments, the surface area of the micron-scale flakes is 50 square microns to 3600 square microns (the surface size of the flakes is in the range of 7 microns to 60 microns) and the thickness is 1 micron to 5 microns.
[0061] In these embodiments, micron-sized flakes with a specific surface area and thickness can effectively micro-melt and accumulate to form an anti-rust layer under the action of a subsequent energy source, matching with the subsequent energy source, thereby facilitating the optimal performance of the anti-rust layer.
[0062] In some embodiments, among the micron-scale flakes, the surface area of the nano-scale flakes is 4900 square nanometers to 360000 square nanometers, and the thickness is 10 nanometers to 50 nanometers. In this way, micron-scale flakes with predetermined gaps can be constructed so that the anti-rust layer formed by the micron-scale flakes has a desired layer gap structure, thereby achieving the purpose of enhancing the anti-rust ability of the anti-rust layer.
[0063] In some embodiments, the gap between adjacent nanoscale scales in the micro-scale flaky material is within the range of 50 nanometers to 200 nanometers. By selecting a micro-scale flaky material with a suitable nanoscale scale gap, the desired interlayer structure can be easily obtained. The micro-scale flaky material is relatively stable in the process of forming the anti-rust layer, and is not prone to large deformation or reorganization, so that the original gap characteristics can be maintained. Since the nanoscale gaps in the micro-scale flaky material are retained, the nanoscale gaps in the interlayer structure of the anti-rust layer formed can also be guaranteed. This optimized interlayer structure helps to reduce the immersion path of the corrosive medium and improve the anti-corrosion performance of the anti-rust layer. In addition, the presence of nanoscale gaps can also improve the durability of the anti-rust layer. When the corrosive medium immerses in the anti-rust layer, they need to pass through these tiny gaps. Because the size of the gap is very small, the corrosive medium will be subject to great resistance when passing through, making it difficult for the corrosive medium to penetrate. In addition, the nanoscale gaps between the micro-scale flaky materials can also increase the adhesion between the anti-rust layer and the substrate. When the anti-rust layer is formed, these gaps can be embedded in the substrate surface like "anchor points", thereby improving the overall bonding strength of the anti-rust layer.
[0064] According to the present application, the micro-scale flaky material is an inorganic non-metallic material having a certain hardness and high temperature resistance, so that the formed anti-rust layer can remain stable under high temperature and wear environment.
[0065] In some embodiments, the inorganic non-metallic material is an oleophilic material, so that it is possible to facilitate the subsequent formation of a fatty acid salt modified layer on its surface. As an example, the inorganic non-metallic material includes micaceous iron oxide or a modified micaceous iron oxide. The above materials have low surface energy and high wear resistance, which can ensure that the anti-rust layer formed therefrom has a certain non-stick durability. In a preferred embodiment, the micaceous iron oxide is gray micaceous iron oxide, which can ensure that the formed anti-rust layer has a relatively dark color, thereby enhancing the product's resistance to dirt and user experience.
[0066] According to the present application, in the anti-rust layer, the interlayer structure has a plurality of micrometer-scale gaps, and a plurality of nanometer-scale gaps are provided between adjacent micrometer-scale gaps.
[0067] Figure 3 This is a scanning electron microscope image of the anti-rust layer provided according to the embodiment of the present application. Figure 4 Schematic diagram of the structure of the anti-rust layer provided according to the embodiment of the present application. Figure 3 and Figure 4 It can be roughly seen that adjacent micro-scale flaky materials are stacked in layers to form an anti-rust layer with a fish-scale-like interlayer structure, and it can be seen that the interlayer structure has large gaps (micrometer-level gaps) and small gaps (nanoscale gaps).
[0068] The inventors also found that the gap size and gap distribution in the interlayer structure can greatly affect the corrosion resistance of the formed anti-rust layer.
[0069] According to the present application, the interlayer structure has gaps of multiple levels of size, which are smaller than the size of the micro-scale flaky material, about 1 / 5-1 / 7 of the size of the micro-scale flaky material. In the anti-rust layer, the interlayer structure has not only micron-level gaps, but also nano-level gaps, and there are multiple nano-level gaps between adjacent micron-level gaps. In this way, in the anti-rust layer, nano-level gaps and micron-level gaps can be combined to form a multi-level microstructure, which together constitute a multi-level barrier, which is conducive to making the gaps disconnected from each other in the thickness direction, so that the corrosive medium can be inhibited from continuing to penetrate inward and make the cookware rust-resistant.
[0070] In addition, gaps of different sizes also play a role in regulating and dispersing stress. During the cooking process, cookware is subject to various external forces, such as temperature changes, food pressure, etc. These external forces may cause stress concentration and damage inside the coating. The multi-level and multi-scale gap structure design can effectively disperse these stresses and reduce the impact of stress on the coating, thereby improving the stability and durability of the anti-rust layer.
[0071] In these embodiments, the anti-rust layer having a layer structure with both micrometer-scale gaps and nanometer-scale gaps together constitutes a multi-level barrier, which is beneficial for making the gaps disconnected from each other in the thickness direction. In this way, the corrosive medium can be inhibited from continuing to penetrate inward, making the cookware more rust-resistant.
[0072] In some embodiments, the nano-scale gap is 1 / 45-1 / 55 of the micro-scale gap. As an example, the size of the micro-scale gap is 1 micron-10 microns, and the size of the nano-scale gap is 50 nanometers-200 nanometers.
[0073] In these embodiments, the rust-proof layer having a layer gap structure with both micrometer-scale gaps and nanometer-scale gaps of the above sizes has a higher uniformity of the layer gap structure and can have relatively excellent corrosion resistance.
[0074] In some embodiments, the micron-scale gaps and nano-scale gaps are irregular shapes. Compared with regular gap structures, irregular shapes can provide more surface changes and spatial distributions. On the one hand, they help the staggered arrangement of the layer gap structure in the thickness direction, further enhancing the anti-corrosion ability. On the other hand, they help the gas (such as air and water vapor) to be more evenly distributed and expanded in the gaps, thereby forming a uniform and stable flotation effect, so that the anti-rust layer also has good non-stick properties. Preferably, the irregular shape is a meniscus-shaped gap, which can effectively block and disperse the penetration path of the corrosive medium, increase the difficulty of the corrosive medium penetrating the anti-rust layer, and thus improve the physical barrier performance of the anti-rust layer.
[0075] In some embodiments, the thickness d2 of the anti-rust layer is 10 microns to 150 microns, so that the properties of the cookware in terms of weight, non-stickiness, and thermal conductivity can be balanced, so that the overall performance of the cookware is better. Correspondingly, each sub-layer is set to have the same thickness. As an example, the thickness of each sub-layer can be 5 microns to 50 microns.
[0076] In some embodiments, the hardness of the anti-rust layer is 600 HV to 1100 HV. The anti-rust layer with such hardness can balance wear resistance and flexibility. It has sufficient wear resistance to resist scratches and abrasion, while maintaining good flexibility to avoid cracking or peeling under temperature changes or mechanical stress.
[0077] In some embodiments, the anti-rust layer has a temperature tolerance of 800°C-1200°C. Thus, the cookware having the anti-rust layer is not afraid of high temperatures and has longer durability.
[0078] In some embodiments, the surface energy of the anti-rust layer is 28 mN / m-34 mN / m, so that the cookware with the anti-rust layer can have good initial non-stick properties.
[0079] According to the present application, the anti-rust layer can further improve the non-stick property by means of two principles. Specifically, when grease contacts the anti-rust layer, an oil film layer is easily formed on the surface of the anti-rust layer to further optimize the non-stick property of the cookware.
[0080] According to some embodiments of the present application, a fatty acid salt modified layer is connected to the surface of the anti-rust layer, wherein the fatty acid salt modified layer includes fatty acid salts formed by chemical bonding of grease and metal elements contained in the surface of the anti-rust layer.
[0081] In some embodiments, the oil comprises at least one of stearin, palmitin, and olein.
[0082] In these embodiments, a fatty acid salt modified layer is further connected to the surface of the anti-rust layer. The fatty acid salt modified layer is compatible with oils and fats. Therefore, by utilizing the oil film non-stick principle, the initial non-stick property and the lasting non-stick performance of the cookware are improved to a certain extent.
[0083] According to a second aspect of the present application, a method for manufacturing an anti-rust layer is provided, wherein the method for manufacturing an anti-rust layer comprises:
[0084] Step S102, providing a micro-scale material, wherein the micro-scale material is formed by stacking a plurality of nano-scale flakes.
[0085] Step S103, micro-melting the surface of the micro-flake material, so as to form an anti-rust layer having a plurality of sub-layers stacked in the thickness direction by stacking the micro-flake material, and making the layer gap structures of the respective sub-layers arranged alternately in the thickness direction of the anti-rust layer; wherein the sub-layers have a layer gap structure, the layer gap structure has a plurality of micron-level gaps, and a plurality of nano-level gaps are provided between adjacent micron-level gaps.
[0086] According to the method for manufacturing an anti-rust layer provided in the embodiment of the present application, by using a specific micro-scale flaky material for micro-melting treatment, the micro-scale flaky material is stacked in layers to form an anti-rust layer having a specific interlayer structure and interlayer distribution as described above, and the interlayer structures of the sub-layers of the anti-rust layer are arranged alternately in the thickness direction of the anti-rust layer, so that the anti-rust layer as a whole is formed into a physical barrier layer, which can effectively prevent water vapor, acid, salt and other corrosive media from penetrating toward the base material of the cooker, thereby avoiding affecting the base material of the cooker. At the same time, the anti-rust layer itself has good corrosion resistance, and even if water vapor, acid, salt and other corrosive media exist on the surface of the anti-rust layer, the cooker will not be corroded, so that the corrosion resistance of the cooker can be guaranteed.
[0087] The specific method for manufacturing the anti-rust layer can be understood in conjunction with the method for manufacturing the cooker in the following embodiment.
[0088] According to a third aspect of the present application, a method for manufacturing a cooker is provided, wherein the method for manufacturing the cooker comprises:
[0089] Step S101, providing a substrate.
[0090] Step S102, providing a micro-scale material, wherein the micro-scale material is formed by stacking a plurality of nano-scale flakes.
[0091] Step S103, micro-melting the surface of the micro-scale material to form an anti-rust layer having a plurality of sub-layers stacked in the thickness direction by stacking the micro-scale material, and making the interlayer structures of the sub-layers arranged alternately in the thickness direction of the anti-rust layer.
[0092] Hereinafter, the method for manufacturing the cooker of the present application will be described in detail with reference to specific embodiments.
[0093] Provide substrate
[0094] According to the present application, the substrate 110 can be made of commonly used materials or a composite of multiple materials. For example, the material can be stainless steel, titanium, aluminum, titanium alloy or aluminum alloy. The substrate 110 can have a shape corresponding to the function, for example, Figure 1 As shown in FIG. 1 , when the cooker 100 is a non-stick pan, the base 110 may have a conventional pan shape. It should be understood that Figure 1Only the main body of the non-stick pan is exemplarily shown without showing other parts, and the non-stick pan according to the present invention may also include common cookware structures / components such as a handle (eg, a pot handle).
[0095] According to the present application, the substrate 110 may be pre-treated, for example, grinding, sandblasting, pickling, etc. The substrate 110 has a certain surface roughness, and in an exemplary embodiment, the surface roughness Ra value may be in the range of 3 μm-5 μm.
[0096] In some embodiments, the thickness d1 of the substrate may be in the range of 1.0 mm to 2.5 mm.
[0097] Forming a transition layer (optional)
[0098] According to the present application, a metal material is thermally sprayed to form a transition layer, wherein the spraying method can adopt an existing process for forming a layer. As an example, the spraying method is cold spraying or plasma spraying. In a preferred embodiment, the spraying method is plasma spraying, and the spraying parameters include current, voltage, main gas flow rate, hydrogen flow rate, powder feeding gas flow rate, powder feeding amount, etc. Specifically, the current is 200A-300A; the voltage is 30V-50V; the main gas (argon) flow rate is 1500L / h-2000L / h; the hydrogen flow rate is 40L / h-60L / h; the powder feeding gas flow rate is 25L / h-40L / h; the powder feeding amount is 15g / min-25g / min; the spraying (the distance from the gun nozzle to the workpiece) distance is 15cm-25cm; the spraying angle is 45°-80°; the workpiece temperature is 15℃-25℃.
[0099] In some embodiments, the metal material is titanium, aluminum, iron, titanium alloy, iron alloy or aluminum alloy. As an example, the iron alloy can be stainless steel. By thermally spraying the above metal materials to form a transition layer of the cooker, a transition layer with a certain rough surface can be formed on the substrate, so that the bonding force between the rust-proof layer and the substrate can be improved. In addition, for the selection of metal materials, it can be selected based on the need for tendency. For example, when it is necessary to improve the heating efficiency of the cooker, aluminum with good thermal conductivity can be used as the material for forming the transition layer to improve the heating efficiency by improving the thermal conductivity of the cooker.
[0100] In some embodiments, the metal material is in a granular form. As an example, the particle size of the metal material is between 10 microns and 60 microns, so that it can meet the process requirements of plasma spraying, have good powder feeding fluidity and heat melting properties, and form a transition layer with a preset rough surface. As an example, the shape of the metal material can be spherical or quasi-spherical, so that a relatively dense transition layer can be formed through the principle of spherical close packing to improve thermal conductivity and corrosion resistance.
[0101] In some embodiments, the thickness of the transition layer is 8 micrometers to 80 micrometers. If the thickness of the transition layer is too thin, it is easy to be uneven locally, and the desired rough surface cannot be formed, and the role of the transition layer cannot be played. If the thickness of the transition layer is too thick, a large stress will be generated, resulting in a decrease in bonding strength.
[0102] In some embodiments, the roughness of the surface of the transition layer is 8 microns to 15 microns. Such roughness can ensure the bonding strength of the anti-rust layer thereon.
[0103] Forming anti-rust layer
[0104] According to the present application, the step of forming the anti-rust layer includes micro-melting the surface of the micro-scale material to form an anti-rust layer with a layer structure having multiple micron-scale gaps by stacking the micro-scale material, wherein there are multiple nano-scale gaps between adjacent micron-scale gaps.
[0105] In these embodiments, the surface of the micro-flaky material is slightly melted, which enables the micro-flaky material to be connected to the substrate without damaging the internal structure of the micro-flaky material. In this way, the internal structure of the micro-flaky material can be retained in the anti-rust layer to a large extent, thereby forming a desired interlayer structure to enhance the anti-rust performance.
[0106] According to the present application, the step of forming the anti-rust layer includes the step of preparing a micro-scale material.
[0107] According to the present application, the micro-scale flaky material is an inorganic non-metallic material. The inorganic non-metallic material includes micaceous iron oxide or a modified product of micaceous iron oxide. Here, micaceous iron oxide is not a simple mixture of mica and iron oxide, but an iron ore with ferric oxide (Fe2O3) as the main chemical component. It should be noted that it also contains other elements such as potassium, aluminum, lithium, and magnesium, but its core component is α-Fe2O3, and its crystals are hexagonal in the form of flakes or plates.
[0108] In some embodiments, the micro-flaky material includes, in terms of main components, iron oxide, silicon dioxide, aluminum oxide, potassium oxide, ferroferric oxide, calcium oxide, sodium oxide, magnesium oxide, manganese oxide and titanium oxide, and in terms of weight percentage, 30%≤iron oxide≤50%, 15%≤silicon dioxide≤30%, 4%≤aluminum oxide≤20%, 30%≤potassium oxide≤40%, 0.01%≤ferroferric oxide≤0.08%, 0.08%≤calcium oxide≤0.13%, 0.01%≤sodium oxide≤0.05%, 0.2%≤magnesium oxide≤0.35%, 0.02%≤manganese oxide≤0.13% and 0.21%≤titanium oxide≤0.33%.
[0109] In the embodiment of the present application, iron oxide (Fe2O3) is one of the main components of the micro-scale flaky material, and the weight proportion of iron oxide is between 30% and 50%. Iron oxide not only has anti-rust properties, but also can increase the hardness and wear resistance of the micro-scale flaky material. At the same time, iron oxide has good oleophilic properties, and can be well affinity with grease while preventing rust, providing certain non-stick properties for cookware. The weight proportion of silicon dioxide (SiO2) is between 15% and 30%, which can improve the thermal stability and chemical stability of the micro-scale flaky material. The weight proportion of aluminum oxide (Al2O3) is between 4% and 20%, which can enhance the hardness and wear resistance of the micro-scale flaky material. The weight proportion of potassium oxide (K2O) is between 30% and 40%, and potassium oxide can be used to adjust the conductivity of the micro-scale flaky material or improve its compatibility with other components, and can also reduce the melting point of the micro-scale flaky material, which is convenient for good micro-melting when preparing the anti-rust layer. The weight percentage of ferroferric oxide (Fe3O4) is between 0.01% and 0.08%, which is used to fine-tune the magnetic or electromagnetic properties of the material. It also has a black appearance, which can deepen the blackness of the material and improve the anti-fouling performance of the anti-rust layer. The weight percentage of calcium oxide (CaO) is between 0.08% and 0.13%, which is used to adjust the pH value of the material or as an alkaline component, which helps to improve the corrosion resistance of the micro-scale material. At the same time, calcium ions can form a modified layer of fatty acid salts with grease to provide certain non-stick properties. The weight percentage of sodium oxide (Na2O) is between 0.01% and 0.05%, which is used to adjust the conductivity or compatibility of the material; alkaline metal oxides can also reduce the melting point of the micro-scale material, making it easy to form a micro-melting state when heated. The weight percentage of magnesium oxide (MgO) is between 0.2% and 0.35%, which helps to improve the fire resistance of the micro-scale material; at the same time, magnesium ions can also form fatty acid salts with grease to provide non-stick properties. The weight percentage of manganese oxide (MnO) is between 0.02% and 0.13%, which is used to improve the color of the micro-scale material, ensure that the color of the anti-rust layer is relatively dark, improve the dirt resistance, and ensure user experience. The weight percentage of titanium oxide (TiO2) is between 0.21% and 0.33%, which can improve the whiteness and hiding power of the micro-scale material, and at the same time has certain photocatalytic properties, which helps to improve the antibacterial properties of the material.
[0110] In these embodiments, the micro-scale material having the above ingredients has excellent anti-rust performance, high hardness and wear resistance, and low surface energy, so that the properties of the formed anti-rust layer can be better.
[0111] According to the present application, the step of preparing the micro-scale flaky material may also include the step of manufacturing the micro-scale flaky material.
[0112] In some embodiments, the micro-scale flaky material is mica iron oxide, and the mica iron oxide can be obtained by using the specularite associated with the mica ore as a raw material. Specifically, the ground specularite is reacted with an acid (for example, a sulfuric acid solution with a mass concentration of 10%) in a mass ratio of 40:60 to dissolve the iron element therein and remove impurities. Then, an oxidant (such as chlorine, oxygen, etc.) is added to the solution to oxidize the ferrous ions into ferric ions. An alkali (such as caustic soda) is added to neutralize the solution so that the iron ions are precipitated in the form of ferric hydroxide. Finally, the precipitate is subjected to a hydrothermal treatment (such as treatment in an autoclave), and the ferric hydroxide is converted into mica iron oxide by controlling conditions such as temperature, pressure and reaction time. Finally, the micro-scale flaky material of the desired size is obtained by screening.
[0113] In other embodiments, the micro-scale material is mica iron oxide, which can be obtained by high-temperature vacuum pyrolysis. Specifically, mica and iron salt are evenly mixed in a weight ratio of 60:40, and then the mixed raw materials are pyrolyzed under vacuum conditions of 1100°C-1300°C. In this process, the iron salt decomposes to generate iron oxide, and combines with mica to form mica iron oxide powder. As an example, the iron salt may include ferric chloride and ferric sulfate.
[0114] In some other embodiments, the micro-scale material is mica iron oxide, which can be obtained by the iron oxide sol method. Specifically, ferric chloride or ferric sulfate is selected as the iron source, sodium hydroxide solution is used as the alkali source, and mica aqueous suspension is used as the carrier. Then, ferric chloride or ferric sulfate and sodium hydroxide solution are mixed in a weight ratio of 15:85, and then quickly added to a mica aqueous suspension with a mass concentration of 20%. Then, under appropriate temperature and pressure, a hydrothermal reaction is carried out to combine iron ions with mica to form mica iron oxide. Finally, after the reaction is completed, post-processing steps such as washing, drying and grinding are carried out to obtain the final mica iron oxide powder.
[0115] According to the present application, the mica iron oxide according to the present application can be obtained as a micro-scale flaky material by the above three methods. The mica iron oxide has a micro-scale flaky material with a desired structure, and the iron oxide in the mica iron oxide is α-Fe2O3, has a specific crystal structure, has a large diameter-thickness ratio, a size between 7 microns and 60 microns, and a thickness of 1 micron to 5 microns. This flaky structure enables the mica iron oxide to form a dense coating, which can further improve the anti-corrosion performance. In the present application, the weight ratio of mica and iron oxide in the micro-scale flaky material is (30-60): (40-70).
[0116] According to the present application, the preparation method of the modified mica iron oxide includes first adding 40-50 parts of mica iron oxide to 60-70 parts of an aqueous solution containing 0.8% stearic acid by mass concentration, then placing it in an ultrasonic water bath at 60°C-70°C for heating, stirring and ultrasonic treatment for 0.5h-1h, and then drying with hot air below 100°C to obtain mica iron oxide with a stearic acid modified layer on the surface. Of course, according to the present application, other similar modifiers can also be used to modify mica iron oxide to obtain a modified mica iron oxide.
[0117] According to the present application, the step of micro-melting the surface of the micro-scale material includes plasma spraying the micro-scale material with preset parameters to make the surface of the micro-scale material micro-melted.
[0118] In some embodiments, micro-melting the surface of the micro-flaky material includes: heating the micro-flaky material with plasma, supersonic flame, electric arc or laser as an energy source to cause micro-melting of the surface of the micro-flaky material.
[0119] As an example, the preset parameters of plasma include current of 350A-650A; voltage of 50V-85V; main gas (argon) flow rate of 1000L / h-2000L / h; hydrogen flow rate of 60L / h-80L / h; powder feeding gas flow rate of 35L / h-50L / h; powder feeding amount of 25g / min-35g / min; spraying (distance from gun nozzle to workpiece) distance of 15cm-20cm; spraying angle of 45°-80°; workpiece temperature of 15℃-25℃.
[0120] As an example, the preset parameters for supersonic flame spraying include a fuel flow rate in the range of 24 L / h to 30 L / h, an oxygen flow rate in the range of 51.7 m3 / h to 56 m3 / h, a powder feed rate in the range of 1.4 g / min to 70.0 g / min, and a spraying distance between 300 mm and 380 mm.
[0121] As an example, the preset parameters of arc spraying include a spraying current of 150A-180A; a spraying voltage of 30V-32V; a spraying pressure of 0.45MPa-0.55MPa; and a spraying distance of 100mm-120mm.
[0122] As an example, the preset parameters of laser cladding include laser power of 3KW-4KW, circular or rectangular spot can be selected, the spot is 3mm-5mm away from the workpiece surface, the laser cladding line speed is 20m / min-50m / min, and nitrogen or argon is used as the protective gas.
[0123] In these embodiments, the anti-rust layer can be adapted to be formed by various types of heat sources, thereby being able to broaden the methods of manufacturing the anti-rust layer.
[0124] According to other embodiments of the present application, in order to further improve the corrosion resistance, the size of the micro-flake material of each sub-layer forming the anti-rust layer can also be set, so that each sub-layer is formed by micro-flake material of different sizes, so that the layer gap structure of each sub-layer is arranged alternately in the thickness direction of the anti-rust layer.
[0125] As an example, the size of the micro-scale material forming the relatively inner layer can be relatively larger, and the size of the micro-scale material forming the relatively outer layer can be relatively smaller, or the size of the micro-scale material forming the relatively inner layer can be relatively smaller, and the size of the micro-scale material forming the relatively outer layer can be relatively larger, so that the gaps between the sub-layers of the formed anti-rust layer can be staggered in the thickness direction, so that the gaps between the sub-layers of the anti-rust layer in the thickness direction can not communicate with each other, so that it can act as a barrier layer to prevent the entry of corrosive media, avoid corrosion of the junction between the substrate and the anti-rust layer, and ensure the anti-rust ability of the product with the anti-rust layer. It should be noted that in these embodiments, when the size of the material located on the outside is smaller, it can also inhibit the entry of corrosive media (for example, water molecules), and the anti-rust effect is relatively better.
[0126] In some embodiments, the anti-rust layer includes a plurality of sublayers stacked in the thickness direction, the innermost layer of the plurality of sublayers is used to connect with the base of the cookware, and the outermost layer of the plurality of sublayers is used as the inner surface of the cookware, wherein the micro-scale material includes a plurality of first micron-sized scales and a plurality of second micron-sized scales, wherein the surface area of the first micron-sized scales is greater than the surface area of the second micron-sized scales, and the thickness of the first micron-sized scales is greater than the thickness of the second micron-sized scales.
[0127] As some examples, a first sublayer is formed on the substrate by first micron-sized scales, and then a second sublayer is formed on the first sublayer by second micron-sized scales, so that the interlayer structures of the sublayers of the anti-rust layer are arranged alternately in the thickness direction of the anti-rust layer;
[0128] As some other examples, a first sublayer is formed on a substrate by second micron-scale flakes, and then a second sublayer is formed on the first sublayer by first micron-scale flakes, so that the interlayer structures of the sublayers of the anti-rust layer are arranged alternately in the thickness direction of the anti-rust layer.
[0129] A first sublayer is formed on the substrate with second micron-sized scales, and then a second sublayer is formed on the first sublayer with first micron-sized scales, so that the interlayer structures of the sublayers of the antirust layer are arranged alternately in the thickness direction of the antirust layer.
[0130] In these embodiments, by adopting the same spraying parameters, the smaller micron-sized flakes can be arranged more closely together to form a relatively dense sublayer. This dense structure helps to reduce the penetration path of the corrosive medium and improve the anti-corrosion performance of the anti-rust layer. On the contrary, the larger micron-sized flakes will form a relatively loose sublayer when sprayed. When two different sublayers are stacked in the thickness direction, their gaps tend to be arranged in a staggered manner along the thickness direction of the anti-rust layer. This staggered arrangement helps to form a complex interlayer structure, further increasing the difficulty of penetration of the corrosive medium. In addition, the uniformity of the internal pore distribution can be ensured by the staggered interlayer structure, which can more effectively disperse the pressure of the corrosive medium and prevent it from concentrating in a specific area and causing the failure of the anti-rust layer.
[0131] In some embodiments, the surface area of the first micron-scale flakes is 50 square microns to 1000 square microns, and the thickness is 1 micron to 3 microns, and the surface area of the second micron-scale flakes is 1000 square microns to 3600 square microns, and the thickness is 3 microns to 5 microns. More specifically, the first micron-scale flakes are composed of a plurality of first nanoscale flakes stacked, the surface area of the first nanoscale flakes is 4900 square nanometers to 90000 square nanometers, and the thickness is 10 nanometers to 30 nanometers; and / or the second micron-scale flakes are composed of a plurality of second nanoscale flakes stacked, the surface area of the second nanoscale flakes is 90000 square nanometers to 360000 square nanometers, and the thickness is 30 nanometers to 50 nanometers.
[0132] In these embodiments, the arrangement of the interlayer structure can be further optimized through micro-flake materials with specific parameters to ensure better anti-rust performance.
[0133] Forming oil film
[0134] According to the present application, before the step of forming the oil film layer, the anti-rust layer may be polished and ground to make the surface bright and smooth, which is convenient for subsequent stir-frying operations.
[0135] According to the present application, the anti-rust layer can achieve non-stick properties through the flotation effect, and can also achieve non-stick properties with the help of the oil film principle. In this way, the non-stick properties of the anti-rust layer are optimized through the two non-stick principles, and excellent non-stick properties can be obtained.
[0136] At present, compared with the oil film layer formed by physical bonding, the bonding force between the chemically bonded oil film modification layer and the substrate is strong, and the oil film layer itself has high hardness and wear resistance, so it can maintain its non-stickiness for a long time during use. Even if it is affected by external factors such as high temperature and grease during use, the oil film layer is not easy to deteriorate or fail. This makes the chemically bonded oil film modification layer show better performance in terms of long-lasting non-stickiness. The acidity of grease is weak, and the ions on the surface of the substrate are mostly in atomic state. Therefore, it is usually impossible to form chemical bonds through acid-base reactions. On the contrary, it is more inclined to bind to the metal surface through physical adsorption or weak chemical adsorption.
[0137] According to the present application, the oil is at least one of stearic acid glyceryl, palmitic acid glyceryl and oleic acid glyceryl, the oil is brought into contact with the treated anti-rust layer, and a modified layer is formed on the surface of the anti-rust layer by chemical bonding, and these modified layers will further optimize the non-stick properties of the cookware with the help of the oil film non-stick principle.
[0138] According to the present application, the method for manufacturing the cookware also includes oxidizing the substrate to form an oxide film on its surface. This oxide film not only improves the activity of the metal surface, but also provides a reaction site for the subsequent grafting of fatty acid salts. The oxidation treatment method may include micro-arc oxidation, anodizing, gas oxidation, etc., and the specific selection depends on the material of the substrate and the required performance. The 0-valent metal atoms on the surface of the substrate are oxidized into high-valent metal ions to increase the activity of the metal surface and facilitate subsequent chemical bonding with fatty acids. At the same time, the metal oxide film has a high hardness and can enhance the resistance to scraping and durability of the anti-rust layer.
[0139] Specifically, an appropriate oxidation treatment method is selected, such as micro-arc oxidation, anodic oxidation, gas oxidation and salt bath oxidation, etc. For aluminum and its alloys, micro-arc oxidation or anodic oxidation is preferred; for stainless steel, gas oxidation is preferred.
[0140] According to the present application, the manufacturing method of the cooker also includes a hydration treatment after the substrate is subjected to a preliminary oxidation treatment. Specifically, after the oxidation treatment, a layer of oxide film will be formed on the surface of the anti-rust layer. In order to improve the activity of the oxide film, water vapor can be used to perform a hydration oxidation treatment on it. Water vapor reacts with metal oxides to generate hydrated oxides. During this process, the oxide film will expand in volume and produce a large number of hydroxyl groups (-OH). These hydroxyl groups are highly active functional groups and are easy to react with other compounds. When combined with fatty acids, these hydroxyl groups can undergo an esterification reaction with the carboxyl group (-COOH) in the fatty acid. Esterification is a chemical reaction that forms ester compounds, in which the carboxyl group combines with the hydroxyl group to form an ester bond (-COO-) and water.
[0141] Specifically, the anti-rust layer is a mica iron oxide layer, which can contain calcium and magnesium metal ions after oxidation and water vapor treatment. The oil contains free fatty acids, and the carboxyl groups in the fatty acids can combine with calcium and magnesium ions to form fatty acid calcium or fatty acid magnesium, which are then deposited and attached to the surface of the anti-rust layer to form fatty acid salts.
[0142] According to some embodiments of the present application, a fatty acid salt modified layer is connected to the surface of the interlaminar structure, and the fatty acid salt modified layer includes fatty acid salts formed by chemical bonding of grease and metal elements contained in the surface of the anti-rust layer.
[0143] In these embodiments, by performing oxidation treatment and water vapor treatment on the inner surface of the substrate, a hydrated oxide film containing water and oxides can be generated on the surface of the anti-rust layer. This film can not only seal the pores in the oxide film, improve the compactness and corrosion resistance of the substrate, but also produce a large number of hydroxyl groups, providing reaction sites for the esterification reaction with fatty acids. Through the esterification reaction, a strong chemical bond is formed between the fatty acid and the substrate, thereby further improving the adhesion and durability of the oil film layer.
[0144] In some embodiments, the thickness of the fatty acid salt modified layer is 0.08 micrometers to 0.12 micrometers. Such a thickness can be maintained for a long time to improve the non-stick property of the cookware.
[0145] According to a fourth aspect of the present application, a cooking utensil is provided, wherein: Figure 1 and Figure 2 As shown, the cooker includes a base 110 and an anti-rust layer 120 formed on the base, and the anti-rust layer 120 includes the anti-rust layer provided according to the above embodiment.
[0146] In some embodiments, the cookware further includes a transition layer 130 , which is formed of a metal material and is formed between the base and the anti-rust layer.
[0147] In these embodiments, by providing a transition layer, the bonding strength between the anti-rust layer and the substrate can be further improved.
[0148] In some embodiments, the metal material is titanium, aluminum, iron, titanium alloy, iron alloy or aluminum alloy. There are many materials for forming the transition layer, and a preference can be made based on manufacturing requirements. For example, when hardness needs to be improved at the same time, titanium alloy and iron alloy can be selected. The thickness of the transition layer is 8 microns to 80 microns. The transition layer can provide sufficient strength and adhesion without being too thick to affect the overall performance of the cooker.
[0149] The present application will be described in detail below in conjunction with specific embodiments, but the protection scope of the present application is not limited to the embodiments.
[0150] Example 1
[0151] The cookware according to Example 1 was manufactured by the following method.
[0152] Step S10, preparing a cookware base. Specifically, the step of preparing the cookware base includes deep drawing the aluminum alloy, alkali washing and degreasing the surface, drying, and sandblasting, thereby obtaining an aluminum cookware base with a thickness of 1.5 mm as the cookware base.
[0153] Step S20, performing sandblasting on the inner surface of the aluminum pot substrate to control the roughness of the inner surface to 4 microns.
[0154] Step S30, using titanium particles with an average particle size of 10 microns to form a transition layer with a thickness of 30 microns and a roughness of 8 microns on the inner surface of the cookware substrate by plasma spraying technology. The parameters of the plasma spraying process are: current of 250A, voltage of 40V, main gas (argon) flow rate of 1700L / h, hydrogen flow rate of 50L / h, powder feeding gas flow rate of 30L / h, powder feeding amount of 20g / min, spraying distance of 20cm, spraying angle of 40°, and workpiece temperature of 20°C.
[0155] Step S40, prepare gray mica iron oxide flakes as micro-flaky materials, wherein the mica iron oxide flakes have an average surface area of 900 square microns and an average thickness of 3 microns, each scale is formed by stacking multiple nanoscale flakes, and the average surface area of the nanoscale flakes is 260,000 square nanometers and the average thickness is 40 nanometers.
[0156] Step S50, spraying with micro-scale material. Specifically, plasma spraying technology is used to spray micro-scale material on the transition layer to form an anti-rust layer with an average thickness of 20 microns. The spraying parameters of plasma spraying are: current is 600A; voltage is 80V; main gas (argon) flow rate is 2000L / h; hydrogen flow rate is 70L / h; powder feeding gas flow rate is 40L / h; powder feeding amount is 30g / min; spraying distance is 20cm; spraying angle is 40°; workpiece temperature is 20°C, thereby completing the manufacture of the pot of Example 1.
[0157] Example 2
[0158] The cookware of Example 2 is manufactured by the same method as Example 1, except that in step S40, different micro-flaky materials are used (the micro-flaky materials of this embodiment have the same primary structure as the micro-flaky materials of Example 1, and only the surface area of the secondary structure is different. The specific parameters include: the average surface area of the scales is 900 square microns, the average thickness is 3 microns, and each scale is formed by stacking a plurality of nanoscale scales, the average surface area of the nanoscale scales is 360,000 square nanometers, and the average thickness is 40 nanometers) to replace the micro-flaky materials of Example 1.
[0159] Example 3
[0160] The cookware of Example 3 is manufactured in the same method as Example 1, except that in step S40, different micro-flaky materials are used (the micro-flaky materials of this embodiment have the same primary structure as the micro-flaky materials of Example 1, and only the surface area of the secondary structure is different. The specific parameters include: the average surface area of the scales is 900 square microns, the average thickness is 3 microns, and each scale is formed by stacking a plurality of nanoscale scales, the average surface area of the nanoscale scales is 4900 square nanometers, and the average thickness is 40 nanometers) to replace the micro-flaky materials of Example 1.
[0161] Example 4
[0162] The cookware of Example 4 is manufactured by the same method as Example 1, except that in step S40, different micro-flaky materials are used (the micro-flaky materials of this embodiment have the same primary structure as the micro-flaky materials of Example 1, and only the average thickness of the secondary structure is different. The specific parameters include: the average surface area of the scales is 900 square microns, the average thickness is 3 microns, and each scale is formed by stacking a plurality of nanoscale scales, the average surface area of the nanoscale scales is 260,000 square nanometers, and the average thickness is 10 nanometers) to replace the micro-flaky materials of Example 1.
[0163] Example 5
[0164] The cookware of Example 5 is manufactured in the same method as Example 1, except that in step S40, different micro-flaky materials are used (the micro-flaky materials of this embodiment have the same primary structure as the micro-flaky materials of Example 1, and only the average thickness of the secondary structure is different. The specific parameters include: the average surface area of the scales is 900 square microns, the average thickness is 3 microns, and each scale is formed by stacking a plurality of nanoscale scales, the average surface area of the nanoscale scales is 260,000 square nanometers, and the average thickness is 50 nanometers) to replace the micro-flaky materials of Example 1.
[0165] Example 6
[0166] The cookware of Example 6 is manufactured in the same method as Example 1, except that in step S40, different micro-flaky materials are used (the micro-flaky materials of this embodiment have the same secondary structure as the micro-flaky materials of Example 1, and only the surface area of the primary structure is different. The specific parameters include: the average surface area of the scales is 3600 square microns, the average thickness is 3 microns, and each scale is formed by stacking a plurality of nanoscale scales, the average surface area of the nanoscale scales is 260,000 square nanometers, and the average thickness is 40 nanometers) to replace the micro-flaky materials of Example 1.
[0167] Example 7
[0168] The cookware of Example 7 is manufactured in the same method as Example 1, except that in step S40, different micro-flaky materials are used (the micro-flaky materials of this embodiment have the same secondary structure as the micro-flaky materials of Example 1, and only the surface area of the primary structure is different. The specific parameters include: the average surface area of the scales is 50 square microns, the average thickness is 3 microns, and each scale is formed by stacking a plurality of nanoscale scales, the average surface area of the nanoscale scales is 260,000 square nanometers, and the average thickness is 40 nanometers) to replace the micro-flaky materials of Example 1.
[0169] Example 8
[0170] The cookware of Example 8 is manufactured by the same method as Example 1, except that in step S40, different micro-flaky materials are used (the micro-flaky materials of this embodiment have the same secondary structure as the micro-flaky materials of Example 1, and only the average thickness of the primary structure is different. The specific parameters include: the average surface area of the scales is 900 square microns, the average thickness is 1 micron, and each scale is formed by stacking a plurality of nanoscale scales, the average surface area of the nanoscale scales is 260,000 square nanometers, and the average thickness is 40 nanometers) to replace the micro-flaky materials of Example 1.
[0171] Example 9
[0172] The cookware of Example 9 is manufactured in the same method as Example 1, except that in step S40, different micro-flaky materials are used (the micro-flaky materials of this embodiment have the same secondary structure as the micro-flaky materials of Example 1, and only the average thickness of the primary structure is different. The specific parameters include: the average surface area of the scales is 900 square microns, the average thickness is 5 microns, and each scale is formed by stacking a plurality of nanoscale scales, the average surface area of the nanoscale scales is 260,000 square nanometers, and the average thickness is 40 nanometers) to replace the micro-flaky materials of Example 1.
[0173] Example 10
[0174] The cookware of Example 10 is manufactured in the same method as Example 1, except that in step S40, different micro-flaky materials are used (the micro-flaky materials of this embodiment have the same secondary structure as the micro-flaky materials of Example 1, and only the primary structure is different. The specific parameters include: the average surface area of the scales is 50 square microns, the average thickness is 1 micron, and each scale is formed by stacking a plurality of nanoscale scales, the average surface area of the nanoscale scales is 260,000 square nanometers, and the average thickness is 40 nanometers) to replace the micro-flaky materials of Example 1.
[0175] Embodiment 11
[0176] The cookware of Example 11 is manufactured in the same method as Example 1, except that in step S40, different micro-flaky materials are used (the micro-flaky materials of this embodiment have the same secondary structure as the micro-flaky materials of Example 1, and only the primary structure is different. The specific parameters include: the average surface area of the scales is 3600 square microns, the average thickness is 5 microns, and each scale is formed by stacking a plurality of nanoscale scales, the average surface area of the nanoscale scales is 260,000 square nanometers, and the average thickness is 40 nanometers) to replace the micro-flaky materials of Example 1.
[0177] Example 12
[0178] The cookware of Example 12 is manufactured by the same method as that of Example 1, except that in step S10, a different material (the material of the cookware base in this embodiment is titanium alloy) is used to manufacture the cookware base of Example 1.
[0179] Example 13
[0180] The cookware of Example 13 is manufactured by the same method as that of Example 1, except that in step S10, a different material (the material of the cookware base in this embodiment is stainless steel) is used to manufacture the cookware base of Example 1.
[0181] Embodiment 14
[0182] The cookware of Example 14 is manufactured on the cookware substrate in the same manner as in Example 1, except that the average thickness of the anti-rust layer is 150 μm.
[0183] Embodiment 15
[0184] The cookware of Example 15 was manufactured on the cookware substrate in the same manner as in Example 1, except that the average thickness of the antirust layer was 100 μm.
[0185] Example 16
[0186] The cookware of Example 16 is manufactured on the cookware substrate by the same method as in Example 1, except that after step S50, the anti-rust layer is further treated by oxidation and hydration, so that stearin is in contact with the treated anti-rust layer to form a fatty acid modified layer with an average thickness of 0.08 μm on the anti-rust layer.
[0187] Embodiment 17
[0188] The cookware of Example 17 is manufactured on the cookware substrate by the same method as Example 1, except that after step S50, the anti-rust layer is further treated by oxidation and hydration, so that stearin is in contact with the treated anti-rust layer to form a fatty acid modified layer with a thickness of 0.12 microns on the anti-rust layer.
[0189] Embodiment 18
[0190] The cookware of Example 18 is manufactured by the same method as in Example 1, except that in step S40, different micro-flaky materials are used to replace the micro-flaky materials of Example 1, and the anti-rust layers are formed with the above two materials respectively. The cookware of Example 18 is manufactured by the same method as in Example 1, except that the micro-flaky materials of Example 1 are replaced by different micro-flaky materials (the micro-flaky materials of this embodiment include a plurality of first micron-sized flakes and a plurality of second micron-sized flakes, wherein the first micron-sized flakes have an average surface area of 50 square microns-900 square microns, and an average thickness of 1 micron to 2 microns, and the second micron-sized flakes have an average surface area of 900 square microns-3600 square microns, and an average thickness of 3 microns to 5 microns, and the first micron-sized flakes are used to form a first sublayer with a thickness of 10 microns on the substrate, and then the second micron-sized flakes are used to form a second sublayer with a thickness of 10 microns on the first sublayer, thereby obtaining an anti-rust layer in which the interlayer structures of the sublayers are arranged alternately in the thickness direction of the anti-rust layer). The anti-rust layers are formed with the above two materials respectively.
[0191] Embodiment 19
[0192] The cookware of Example 19 is manufactured by the same method as Example 18, except that in step S40, different micro-flaky materials (a first sublayer with a thickness of 10 microns is formed on the substrate with second micron-sized scales, and then a second sublayer with a thickness of 10 microns is formed on the first sublayer with first micron-sized scales, thereby obtaining an anti-rust layer in which the layer gap structures of each sublayer are arranged alternately in the thickness direction of the anti-rust layer) are used to replace the micro-flaky materials of Example 1, and the anti-rust layers are formed respectively with the above two materials.
[0193] Comparative Example 1
[0194] The cookware of Comparative Example 1 is manufactured using the same method as Example 1, except that in step S40, a different material (the material in this embodiment is phlogopite, wherein the phlogopite is flaky, the average surface area of a single scale is in the range of 1 square micron-5 square microns, and the average thickness is 3 microns) is used to replace the micro-flaky material of Example 1.
[0195] Comparative Example 2
[0196] The cookware of Comparative Example 2 is manufactured using the same method as Example 1, except that in step S40, a different material (the material in this embodiment is lithium iron mica, wherein the lithium iron mica is flaky, the average surface area of a single scale is in the range of 1 square micron-5 square microns, and the average thickness is 3 microns) is used to replace the micro-flaky material of Example 1.
[0197] Comparative Example 3
[0198] The cookware of Comparative Example 3 is manufactured using the same method as Example 1, except that in step S40, a different material (the material in this embodiment is hydroxyferric mica, wherein the hydroxyferric mica is flaky, the average surface area of a single scale is in the range of 1 square micron-5 square microns, and the average thickness is 3 microns) is used to replace the micro-flaky material of Example 1.
[0199] Comparative Example 4
[0200] The cookware of Comparative Example 4 is manufactured using the same method as Example 1, except that in step S40, a different material (the material in this embodiment is biotite, wherein the biotite is flaky, the average surface area of a single flake is in the range of 1 square micron-5 square microns, and the average thickness is 3 microns) is used to replace the micro-flaky material of Example 1.
[0201] Comparative Example 5
[0202] The cookware of Comparative Example 5 is manufactured using the same method as Example 1, except that in step S40, a different material (the material in this embodiment is lithium mica, wherein the lithium mica is flaky, the average surface area of a single scale is in the range of 1 square micron-5 square microns, and the average thickness is 3 microns) is used to replace the micro-flaky material of Example 1.
[0203] Comparative Example 6
[0204] The cookware of Comparative Example 6 is manufactured using the same method as Example 1, except that in step S40, a different material (the material in this embodiment is kaolinite, wherein the kaolinite is flaky, the average surface area of a single scale is in the range of 1 square micron to 5 square microns, and the average thickness is 3 microns) is used to replace the micro-flaky material of Example 1.
[0205] Comparative Example 7
[0206] The cookware of Comparative Example 7 is manufactured by the same method as Example 1, except that in step S40, a different material (the material in this embodiment is phlogopite, wherein the phlogopite is flaky, has no secondary structure, the average surface area of the scales is 900 square microns, and the average thickness is 3 microns) is used to replace the micro-flaky material of Example 1.
[0207] Comparative Example 8
[0208] The cookware of Comparative Example 8 is manufactured by the same method as Example 1, except that in step S40, a different material (the material in this embodiment is lithium iron mica, wherein the lithium iron mica is flaky, has no secondary structure, and the average surface area of the scales is 900 square microns and the average thickness is 3 microns) is used to replace the micro-flaky material of Example 1.
[0209] Comparative Example 9
[0210] The cookware of Comparative Example 9 is manufactured by the same method as Example 1, except that in step S40, a different material (the material in this embodiment is hydroxyferric mica, wherein the hydroxyferric mica is flaky, has no secondary structure, and the average surface area of the scales is 900 square microns and the average thickness is 3 microns) is used to replace the micro-flaky material of Example 1.
[0211] Comparative Example 10
[0212] The cookware of comparative example 10 is manufactured by the same method as in example 1, except that in step S40, a different material (the material in this example is biotite, wherein the biotite is flaky, has no secondary structure, the average surface area of the scales is 900 square microns, and the average thickness is 3 microns) is used to replace the micro-flaky material of example 1.
[0213] Comparative Example 11
[0214] The cookware of Comparative Example 11 is manufactured by the same method as Example 1, except that in step S40, a different material (the material in this embodiment is lithium mica, wherein the lithium mica is flaky, has no secondary structure, the average surface area of the scales is 900 square microns, and the average thickness is 3 microns) is used to replace the micro-flaky material of Example 1.
[0215] Comparative Example 12
[0216] The cookware of Comparative Example 12 was manufactured in the same manner as in Example 6, except that after step S40, the substrate was heated to 80° C., peanut oil was applied on the antirust layer and kept for 5 minutes, the surface of the antirust layer was subsequently wiped with a rag, and the substrate was placed in a sintering chamber at 280° C. for 1 minute.
[0217] The cookware in Examples 1 to 19 and Comparative Examples 1 to 12 were tested, and the test results are shown in Table 1 below.
[0218] 1. Test methods and evaluation criteria
[0219] 1. Initial non-stick test method and evaluation criteria
[0220] Initial non-stickiness test method: GB / T32095.2-2015 fried egg non-stickiness test method. This method is an initial non-stickiness test, which is divided into levels Ⅰ, Ⅱ, and Ⅲ. Level Ⅰ has the best non-stickiness and level Ⅲ has the worst non-stickiness.
[0221] 2. Test method and evaluation criteria for long-lasting non-stick properties
[0222] Long-lasting non-stick test method: Long-lasting non-stick test method in GB / T32388-2015, the unit is the number of times, the higher the number, the longer the life, the non-stick result is evaluated once every 500 times, and the number of times when it is used to level III is recorded.
[0223] 3. Hardness test method and evaluation standard
[0224] The Vickers hardness test method is used to test the Vickers hardness of the obtained cookware coating, where the hardness value unit is HV. The larger the measured hardness value, the harder the sample is, the stronger the anti-rust layer is in terms of resistance to abrasion by shovels and food materials, and the less likely it is to be worn. Therefore, the service life of the anti-rust layer is longer. Generally speaking, the hardness of the anti-rust layer is expected to be no less than 200HV.
[0225] 4. Corrosion resistance test methods and evaluation standards
[0226] Prepare a 5% sodium chloride solution, add 1 / 3 of the volume of the pot, cover and keep it boiling. Observe the rust on the pot surface every half an hour until obvious rust appears and stop the experiment.
[0227] For the corrosion resistance test, it is expected that the corrosion resistance of the sample can reach more than 2h.
[0228] 2. Test Results
[0229] Table 1 Test results
[0230]
[0231] As can be seen from Table 1, the anti-rust layer formed by stacking inorganic non-metallic materials according to the present application has good non-stickiness, long-lasting non-stickiness, hardness and corrosion resistance. Too large or too small scales will affect the non-stickiness and long-lasting non-stickiness. At the same time, the thickness of the anti-rust layer has a direct impact on the hardness and corrosion resistance. The thicker the anti-rust layer, the higher the hardness and the better the corrosion resistance.
[0232] According to the present application, when the scale size exceeds the selected range, the non-stickiness and long-lasting non-stickiness of the anti-rust layer are significantly reduced, and even fall below the standard requirements. Specifically, when the scales of the micro-flaky material are too large, it will affect the micro-melting effect of the scales during the preparation of the anti-rust layer, resulting in the anti-rust layer being stacked not densely enough, resulting in excessive gaps, which in turn affects the flotation effect of water and air in the gaps, resulting in a decrease in non-stickiness; when the scales of the micro-flaky material are too small, the scales will over-melt during the preparation of the anti-rust layer, resulting in the anti-rust layer being stacked too densely, without appropriate gaps, which will also affect the entry of water and air into the gaps, and the flotation effect cannot be effectively produced, resulting in a deterioration in non-stickiness.
[0233] Although the present invention has been specifically shown and described with reference to exemplary embodiments of the present invention, it will be understood by those skilled in the art that various changes in form and detail may be made herein without departing from the spirit and scope of the present invention as defined by the claims and their equivalents. The embodiments should be considered in a descriptive sense only and not for the purpose of limitation. Therefore, the scope of the present invention is not limited by the specific embodiments of the present invention, but by the claims, and all differences within the scope will be interpreted as included in the present invention.
Claims
1. A rust-proof layer, characterized in that: The anti-rust layer includes a plurality of sub-layers stacked in layers, each of which has a layer gap structure. The layer gap structure is formed by stacking a plurality of micro-scale flaky materials, which are formed by stacking a plurality of nano-scale flaky materials. The layer gap structure has a plurality of micron-scale gaps, and there are a plurality of nano-scale gaps between adjacent micron-scale gaps, wherein the layer gap structures of each sub-layer are arranged alternately in the thickness direction of the anti-rust layer.
2. The anti-rust layer according to claim 1, characterized in that: The size of the micron-scale gap is 1 micron-10 microns; and / or, the size of the nano-scale gap is 50 nanometers-200 nanometers; and / or, the nano-scale gap and the micro-scale gap are irregular shapes.
3. The anti-rust layer according to claim 1, characterized in that: The micro-scale flake material is a micron-sized flake, and the surface area of the micron-sized flake is 50 square microns to 3600 square microns, and the thickness is 1 micron to 5 microns.
4. The anti-rust layer according to claim 1, characterized in that: The surface area of the nanoscale flakes is 4900 square nanometers to 360,000 square nanometers, and the thickness is 10 nanometers to 50 nanometers; and / or, In micro-scale materials, the gaps between adjacent nanoscale scales are in the range of 50 nanometers to 200 nanometers.
5. The anti-rust layer according to claim 1, characterized in that: The micro-scale material is an inorganic non-metallic material.
6. The anti-rust layer according to claim 5, characterized in that: The inorganic non-metallic material includes micaceous iron oxide and / or modified micaceous iron oxide.
7. The anti-rust layer according to claim 1, characterized in that: The thickness of the anti-rust layer is 10 micrometers to 150 micrometers; and / or, The hardness of the anti-rust layer is 600HV to 1100HV; and / or, The rust-proof layer has a temperature tolerance of 800°C to 1200°C.
8. The anti-rust layer according to claim 1, characterized in that: A fatty acid salt modified layer is connected to the anti-rust layer, and the fatty acid salt modified layer includes fatty acid salts formed by chemical bonding of oil and fat with metal elements contained in the surface of the anti-rust layer.
9. The anti-rust layer according to claim 8, characterized in that: The oil comprises at least one of stearin, palmitin and olein.
10. A method for manufacturing an anti-rust layer, characterized in that: The method comprises the following steps: Providing a micro-scale material, wherein the micro-scale material is formed by stacking a plurality of nano-scale flakes; Micro-melting the surface of the micro-scale material to form a rust-proof layer having a plurality of sub-layers stacked in a thickness direction by stacking the micro-scale material, and making the interlayer structures of the sub-layers arranged in a staggered manner in the thickness direction of the rust-proof layer; The sublayer has a layer gap structure, the layer gap structure has a plurality of micrometer-level gaps, and a plurality of nanometer-level gaps are provided between adjacent micrometer-level gaps.
11. The method for manufacturing an anti-rust layer according to claim 10, characterized in that: The step of slightly melting the surface of the micro-scale material comprises: heating the micro-scale material with plasma, supersonic flame, electric arc or laser as an energy source to slightly melt the surface of the micro-scale material.
12. The method for manufacturing an anti-rust layer according to claim 10, characterized in that: The plurality of sub-layers are respectively formed of micro-scale materials of different sizes, so that the interlayer structures of the sub-layers are arranged alternately in the thickness direction of the anti-rust layer.
13. The method for manufacturing an anti-rust layer according to claim 12, characterized in that: The micro-scale flake materials of different sizes include a plurality of first micron-scale flakes and a plurality of second micron-scale flakes, wherein the surface area of the first micron-scale flakes is greater than the surface area of the second micron-scale flakes, and the thickness of the first micron-scale flakes is greater than the thickness of the second micron-scale flakes; wherein a first sublayer is formed by the first micron-sized flakes, and then a second sublayer is formed on the first sublayer by the second micron-sized flakes, so that the interlayer structures of the sublayers of the anti-rust layer are arranged alternately in the thickness direction of the anti-rust layer; or, A first sublayer is formed by the second micron-sized flakes, and then a second sublayer is formed on the first sublayer by the first micron-sized flakes, so that the interlayer structures of the sublayers of the antirust layer are arranged alternately in the thickness direction of the antirust layer.
14. The method for manufacturing an anti-rust layer according to claim 13, characterized in that: The surface area of the first micron-sized scale is 50 square microns to 1000 square microns, and the thickness is 1 micron to 3 microns; and / or, The second micron-sized scale has a surface area of 1000 square microns to 3600 square microns and a thickness of 3 microns to 5 microns; and / or, The first micron-scale flakes are composed of a plurality of first nanoscale flakes stacked in layers, the surface area of the first nanoscale flakes is 4900 square nanometers to 90000 square nanometers, and the thickness is 10 nanometers to 30 nanometers; and / or, The second micron-scale scale is composed of a plurality of second nanoscale scales stacked in layers, and the surface area of the second nanoscale scale is 90,000 square nanometers to 360,000 square nanometers, and the thickness is 30 nanometers to 50 nanometers.
15. A cooking utensil, characterized in that: The cookware includes a substrate and an antirust layer formed on the substrate, wherein the antirust layer includes the antirust layer according to any one of claims 1 to 9 or includes the antirust layer manufactured by the method for manufacturing an antirust layer according to any one of claims 10 to 14.
16. The cooker according to claim 15, characterized in that The cooker also includes: A transition layer is formed of a metal material and is formed between the substrate and the anti-rust layer.